Theoretical Disquisition about the Supervisory Role - Pérez Figueiras, Elfio Manuel (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2015)
The work deals with the points of view of the author around the different perceptions and questions that have been made and make around the supervisory role: is it science?; do you have identity crisis?; It is administrative or pedagogical function?; is occupied only orientation?; It should be changed by another type of activity? On the basis of extensive bibliographic research researcher runs with critical major publications that have been made, mainly in the last fifty years, although by their documentary character at times he ventured on works made before these dates on this field. Analytical values the opinion of the authors that, over time, have expressed their theoretical postulates on these aspects and concluded in each case postulating positions, which objectively, defend the function supervisor as a guarantor of the educational system. To analyze each one of the questions the author establishes the reasons which, in its view, prevent still consider the supervision as science, the because really there is no identity crisis in its actions and the need to understand that that it is a built-in function that deals with the activities of monitoring, evaluation and counseling, non-polarized by any as their concatenation is required to ensure the educational management in all its dimensions. It concludes defending the identity of function against the ideas of changing its essence replaced by other similar actions designated by other terms.